The feeding habits of the Amur whitefish Coregonus ussuriensis in the Amur River, China - Wang, Jilong; Huo, Tangbin; Li, Peilun; Lu, Wanqiao (Frontiers in Environmental Science, 2023)
To study their feeding habits, Coregonus ussuriensis samples were collected seasonally in the Amur River, China. A total of 574 samples were collected, including 200 individuals with empty stomachs. The stomach contents of the remaining 374 samples were identified, counted, weighed, and analyzed. The results showed that the vacuity rate of Coregonus ussuriensis was 34.84% in total; the rates in summer and autumn were higher than in spring and winter. Prey items could be divided into three categories: fish, benthos, and mammals, with 62 taxonomic units. Of these, fish had the highest relative importance index (IRI), followed by benthos and mammals. Specifically, Exopalaemon modestus was the dominant species among the food species of Coregonus ussuriensis, and unidentified fish, Hydropsyche sp., Hemiculter leucisculus, Abbottina rivularis, and Saurogobio dabryi were important species. The average repletion index (RI, %) of Coregonus ussuriensis was highest in autumn (1.86), followed by winter (1.40), summer (1.26), and spring (1.02). The main food of Coregonus ussuriensis was benthos in spring and autumn, and fish in summer and winter. Cluster analysis showed that, according to the similarity level of the bait biological composition, the fork length group samples of Coregonus ussuriensis could be divided into three groups: 210–330 mm, 330–450 mm, and >450 mm. The highest IRI% of feed organisms in these three groups of samples were fish (73.67%), benthos (75.12%), and benthos (94.46%), respectively. It can be observed that with the growth of the fork length of Coregonus ussuriensis, the importance of benthos in its diet increases. The results of an RDA analysis on the relationship between main bait organisms and various factors indicated that season, river level, river width, and fish size have a significant impact on bait organisms and a positive or negative impact on the quality scores of some bait species. This study filled the gap in biological research on the feeding ecology of Coregonus ussuriensis and laid a research foundation for ecological research on this species and its resource protection and aquaculture.